Empowerment of Housewives of Fisherman through Training on Procesing Squid Production in Lamu Village Gorontalo Regency: Pemberdayaan Ibu-Ibu Rumah Tangga Nelayan Melalui Pelatihan Pembuatan Olahan Cumi di Desa Lamu Kabupaten Gorontalo - Herinda Mardin; Hapsawati Taan; Nur Mustaqimah (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
Lamu Village, Batudaa Pantai District, Gorontalo Regency, which is included in the Tomini Bay area, has abundant potential for marine products such as squid. For this reason, we empower fishermen housewives through training and mentoring activities for fishermen housewives in making processed squid products in the form of squid sauce as an entrepreneurial opportunity in Lamu Village, Batudaa Pantai District, Gorontalo Regency. The purpose of this activity is to add insight and skills regarding the manufacture of processed squid products as a business opportunity and improve the community's economy, especially for fishing housewives in Lamu village. The method used is training and mentoring with an active participatory approach. The result of this activity is that fishermen's housewives already have insight regarding the manufacture of processed squid in the form of squid chili products. This activity provides new knowledge for fishermen housewives that squid sauce can be made into a product that can be marketed in the community and is an opportunity for MSME businesses. Squid chili products are accepted by the public from the aspects of color, taste, aroma and texture of chili in the likes category. The training activity for making processed squid was successfully carried out, seen from the participants who enthusiastically took part in the training activities and the acceptance of participants in the category of liking processed squid products. Abstrak Desa Lamu Kecamatan Batudaa Pantai kabupaten Gorontalo yang masuk dalam kawasan teluk Tomini memiliki potensi hasil laut yang melimpah seperti cumi-cumi. Untuk itu, kami melakukan pemberdayaan ibu-ibu rumah tangga nelayan melalui kegiatan pelatihan dan pendampingan bagi ibu-ibu rumah tangga nelayan dalam membuat produk olahan cumi berupa sambal cumi sebagai peluang wirausaha di desa Lamu Kecamatan Batudaa Pantai Kabupaten Gorontalo. Tujuan kegiatan ini adalah menambah wawasan dan keterampilan mengenai pembuatan produk olahan cumi sebagai peluang usaha dan meningkatkan perekonomian masyarakat khususnya bagi ibu-ibu rumah tangga nelayan di desa Lamu. Metode yang digunakan adalah pelatihan dan pendampingan berpendekatan partisipatif aktif. Hasil kegiatan ini adalah ibu-ibu rumah tangga nelayan sudah memiliki wawasan terkait pembuatan olahan cumi dalam bentuk produk sambal cumi. Kegiatan ini memberikan pengetahuan baru bagi ibu-ibu rumah tangga nelayan bahwa sambal cumi dapat dijadikan sebuah produk yang dapat dipasarkan di masyarakat dan merupakan peluang usaha UMKM. Produk sambal cumi diterima oleh masyarakat dari aspek warna, rasa, aroma dan tekstur sambal pada kategori suka. Kegiatan pelatihan pembuatan olahan cumi ini berhasil dilaksanakan dilihat dari peserta yang antusias mengikuti kegiatan pelatihan serta penerimaan peserta pada kategori suka terhadap produk olahan cumi.